Efektifitas Jumlah Pasangan Elektroda Aluminium pada Proses Elektrokoagulasi terhadap Penurunan Kadar Fosfat Limbah Cair Laundry - Puji Lestari; Choirul Amri; Sigid Sudaryanto (Poltekkes Kemenkes Yogyakarta, 2017)
Since one of the detergent-forming chemicals is phosphate, laundry wastewater contains this substance. In general, laundry businesses do not have waste treatment facilities, while high le-vel of phosphate which is accumulated continuously in waters may lead to eutrophication that disrupting aquatic ecosystems and causing river sedimentation. One of the methods to de-crease phosphate level from laundry wastewater is electrocoagulation, with aluminum plate as the electrode.The research was a true experiment and was aimed to know the decrease of phosphate levels in laundry wastewater yielded from “Rumah Laundry” located at Pajimatan, Imogiri, Bantu, after treated by electrocoagulation process with 3 pairs, 4 pairs and 5 pairs of aluminum electrode. The design of the research was pre-test post-test with control group in five times replications, on randomly selected treatment and control groups. The statistical test with paired t-test shows that the electrocoagulation process is able to reduce the phosphate levels in laundry waste water compared with those of the control (p-value < 0,05). By using the 3, 4, and 5 pairs of aluminium electrode, the reduction of phosphate levels were 31,4 %, 33,7 %, and 27,3 %, respectively. It can be seen that the effective decrease was from the 4 pairs of alumini-um electrode with 12 volt voltage and 500 mA current strength. However, the one way Anava test on those results of the three different electrode pairs shows no significant differences (p-va-lue > 0,05).